2015
DOI: 10.1371/journal.ppat.1004589
|View full text |Cite
|
Sign up to set email alerts
|

Compartment-Specific and Sequential Role of MyD88 and CARD9 in Chemokine Induction and Innate Defense during Respiratory Fungal Infection

Abstract: Aspergillus fumigatus forms ubiquitous airborne conidia that humans inhale on a daily basis. Although respiratory fungal infection activates the adaptor proteins CARD9 and MyD88 via C-type lectin, Toll-like, and interleukin-1 family receptor signals, defining the temporal and spatial pattern of MyD88- and CARD9-coupled signals in immune activation and fungal clearance has been difficult to achieve. Herein, we demonstrate that MyD88 and CARD9 act in two discrete phases and in two cellular compartments to direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 75 publications
8
123
2
Order By: Relevance
“…Notably, CARD9-deficient neutrophils exhibited normal capacity to internalize conidia ( Figure 5), to prevent conidial germination to hyphae (Supplemental Figure 2), and to kill opsonized or unopsonized conidia and hyphae ( Figure 5), in agreement with intact anti-Aspergillus killing of Card9 -/-mouse neutrophils (28). Furthermore, CARD9-deficient neutrophils had normal oxidative burst towards fungal and nonfungal stimuli ex vivo (Supplemental Figure 3), and exerted oxidative cytotoxicity on the B-5233/GFP Aspergillus strain that expresses GFP during oxidative stress (Supplemental Figure 3).…”
Section: Card9 Deficiency Does Not Impair the Anti-aspergillus Effectsupporting
confidence: 61%
See 2 more Smart Citations
“…Notably, CARD9-deficient neutrophils exhibited normal capacity to internalize conidia ( Figure 5), to prevent conidial germination to hyphae (Supplemental Figure 2), and to kill opsonized or unopsonized conidia and hyphae ( Figure 5), in agreement with intact anti-Aspergillus killing of Card9 -/-mouse neutrophils (28). Furthermore, CARD9-deficient neutrophils had normal oxidative burst towards fungal and nonfungal stimuli ex vivo (Supplemental Figure 3), and exerted oxidative cytotoxicity on the B-5233/GFP Aspergillus strain that expresses GFP during oxidative stress (Supplemental Figure 3).…”
Section: Card9 Deficiency Does Not Impair the Anti-aspergillus Effectsupporting
confidence: 61%
“…The absence of pulmonary Aspergillus involvement in CARD9 deficiency may be explained by lung-specific, CARD9-independent immune mechanisms that may compensate for lack of CLR/CARD9 signaling. Indeed, recent mouse studies showed that Card9 plays only a partial role in neutrophil pulmonary recruitment after Aspergillus challenge, being compensated by mononuclear phagocyte and epithelial cell IL-1α and Myd88 signaling (28,33). Thus, CARD9 appears to mediate organ-specific effects on neutrophil recruitment during aspergillosis, being largely redundant for pulmonary recruitment (28) but necessary for recruitment into extrapulmonary organs (current study), in agreement with its CNS-specific role in mediating neutrophil recruitment during systemic candidiasis (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CARD9 is critical for neutrophil recruitment to the Candidainfected CNS but not for neutrophil recruitment to the Candida-infected kidney or Staphylococcus-infected CNS (159). This tropism is mediated by CARD9-dependent production of CXC chemokines by resident glial cells and neutrophils in the Candida-infected CNS, while neutrophil-intrinsic chemotaxis and effector functions are largely intact in CARD9-deficient humans and mice (159)(160)(161). Development of CNS and intra-abdominal aspergillosis is another example of altered tissue tropism in CARD9-deficient patients (162) and results from defective CARD9-dependent neutrophil chemoattractant production in and neutrophil mobilization to extrapulmonary infection sites.…”
Section: Antifungal Immunity: Lessons From Fungal Disease-associated mentioning
confidence: 99%
“…Development of CNS and intra-abdominal aspergillosis is another example of altered tissue tropism in CARD9-deficient patients (162) and results from defective CARD9-dependent neutrophil chemoattractant production in and neutrophil mobilization to extrapulmonary infection sites. The absence of pulmonary Aspergillus involvement in CARD9 deficiency may be explained by compensatory IL-1R/MyD88-dependent neutrophil lung recruitment (161,163). Collectively, these human observations have led to our appreciation that CARD9 appears to mediate fungus-, cell type-, and organ-specific neutrophil recruitment during invasive fungal infection.…”
Section: Antifungal Immunity: Lessons From Fungal Disease-associated mentioning
confidence: 99%